2008
DOI: 10.1167/iovs.07-1361
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex I Defect Induces ROS Release and Degeneration in Trabecular Meshwork Cells of POAG Patients: Protection by Antioxidants

Abstract: The authors propose that a mitochondrial complex I defect is associated with the degeneration of TM cells in patients with POAG, and antioxidants and MPT inhibitors can reduce the progression of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 52 publications
3
97
0
3
Order By: Relevance
“…The profound decline in complex I activity occurring after CS/Tx is significant because complex I has been shown to be a major source of ROS in many diseases [17][18][19]. In addition, complex III, which was also inactivated after CS/Tx, also participates in ROS generation [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The profound decline in complex I activity occurring after CS/Tx is significant because complex I has been shown to be a major source of ROS in many diseases [17][18][19]. In addition, complex III, which was also inactivated after CS/Tx, also participates in ROS generation [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…ATP levels ATP levels were determined using a luciferin/ luciferase-based assay as described [56]. Cells from confluent RPE cultures were harvested and 1×10 5 cells from each sample in an age group seeded into wells of a 96-well plate in SFM for 24 h. Culture medium was then removed, cell membranes permeabilized using 50 μl of somatic cell ATP-releasing reagent, and samples incubated with 50 μl ATPAssay Mix Reagent containing luciferin and luciferase.…”
Section: Age-related Changes In Mitochondrial Functionmentioning
confidence: 99%
“…Mitochondrial membrane potential Mitochondrial membrane potential (Δψm) measurements were carried out as we have described [56] using the indicator JC-1, a lipophilic, and cationic dye which fluoresces red when it aggregates in the matrix of healthy, high-potential mitochondria, and green in cells with low ΔΨm. Cells from confluent RPE cultures were harvested and JC-1 (1 μg/ml) added to 2×10 6 cells/ml in suspension.…”
Section: Age-related Changes In Mitochondrial Functionmentioning
confidence: 99%
“…Interestingly, we have found mitochondrial dysfunction with electron transport chain complex I deficiency in skeletal muscle of TR4 Ϫ/Ϫ mice (Liu S, Lee, YF, Chou S, Uno H, Li G, Brookes P, Massett MP, Wu Q, Chen LM, and Chang C, unpublished observations). It has been reported that a complex I defect induces ROS release in primary open-angle glaucoma patients (16). Is it possible that the complex I defect accounts for the increased oxidative stress in TR4 Ϫ/Ϫ mice and finally leads to premature aging?…”
Section: Discussionmentioning
confidence: 99%